2016
DOI: 10.1007/s12671-016-0540-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness Training on Emotional Health in Chinese Long-Term Male Prison Inmates

Abstract: Long-term imprisonment can cause severe emotional problems, which in turn can trigger behavioral problems, self-harm, and suicide. Mindfulness-based intervention can enhance emotional health. This study investigated the effects of a 6-week mindfulness training program on the emotional health of long-term male Chinese prison inmates. Forty long-term male prisoners completed a pretest and posttest, with 19 in the mindfulness training group and 21 in the waitlist control group. The treatment group showed a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 43 publications
2
29
0
5
Order By: Relevance
“…611 These outcomes include clinical disorders and symptoms such as anxiety, 8,12,13 risk of relapse for depression, 14,15 current depressive symptoms, 9 stress, 1618 medical and well-being outcomes such as chronic pain, 19 quality of life, 14,20 and psychological or emotional distress. 21,22 Additionally, MBIs have been shown to work via changes in specific aspects of psychopathology, such as cognitive biases, affective dysregulation, and interpersonal effectiveness. 17,23,24 …”
Section: Introductionmentioning
confidence: 99%
“…611 These outcomes include clinical disorders and symptoms such as anxiety, 8,12,13 risk of relapse for depression, 14,15 current depressive symptoms, 9 stress, 1618 medical and well-being outcomes such as chronic pain, 19 quality of life, 14,20 and psychological or emotional distress. 21,22 Additionally, MBIs have been shown to work via changes in specific aspects of psychopathology, such as cognitive biases, affective dysregulation, and interpersonal effectiveness. 17,23,24 …”
Section: Introductionmentioning
confidence: 99%
“…23, [35][36][37][38] Some studies have also demonstrated that the improvement in the depression and anxiety symptoms paralleled with improvement in the mindfulness. [47][48][49]51,57,60 However, studies that tested MBSR or its modified version and traditional meditation didn't demonstrate significant effect in depressive symptoms, for examples, 'Vipassana mindfulness approach' in alcohol dependent patients, MBSR for depression in prenatal depression, stress coping program based on mindfulness meditation and 'Mindfulness-Based Therapy and Counseling' (MBTC) in nursing students. 57 Most of the controlled trials with positive outcome compared MBIs with 'no treatment' or a 'treatment as usual-TAU' control.…”
Section: Discussionmentioning
confidence: 99%
“…48 One RCT in China slightly modified MBSR/MBCT model in long term prisoners and found significant a difference in mindfulness, anxiety and depression symptoms compared to waitlist control after 8 weeks. 49 Another study in South Korea found that engaging in daily traditional mindful breathing practice for one week was superior to cognitive reappraisal technique and no treatment control in reducing test anxiety. 50…”
Section: Screening and Intervention Studiesmentioning
confidence: 99%
“…Semakin lama masa hukuman yang harus dijalani narapidana, maka kondisi stres juga semakin tinggi (Siswati & Abdurrohim, 2009). Hukuman penjara dalam jangka waktu panjang dapat menyebabkan permasalahan psikologis berat, seperti depresi, hingga mengarah pada perilaku bunuh diri (Xu, Jia, Liu, & Hoffman, 2016). Hal ini didukung hasil penelitian (Wibowo, 2013;Nursanti, 2014) Teori dan berbagai hasil penelitian sejauh ini sepakat bahwa gejala pada gangguan depresi dapat berupa gejala dalam gaya berpikir (kognitif), afektif dan gejala yang terlihat pada fisik, baik psikomotor maupun psikosomatis (Beck & Emery, 1985;Wilkinson, 1992;De Clerq, 1994; American Psychiatric Association [APA], 2003;Garnefski, Kraaij, & Spinhoven, 2002;Bilkser, Wiseman, & Gilbert, 2006 (Rosenhan & Seligman, 1989).…”
unclassified
“…Terapi mindfulness dapat diajarkan pada berbagai kelompok dan individu yang memiliki permasalahan fisik dan psikologis, termasuk narapidana yang berada di penjara (Crane, 2009 (Nyklíček, Dijksman, Lenders, Fonteijn, & Koolen, 2014;Xu et al, 2016).…”
unclassified